Using IBM WebSphere host access transformation services V5 - Braswell, Byron (IBM redbooks., 2004)
IBM WebSphere Host Access Transformation Services (HATS) provides tools to quickly and easily extend your legacy green-screen applications to the Web. HATS makes your 3270 and 5250 applications available as Hypertext Markup Language (HTML) through Web browsers. It also converts your host screens to a Web look and feel. Using HATS, you can improve the workflow and navigation of your host applications without any access or modification to source code. HATS has a development component called HATS Studio, which runs in WebSphere Studio. There is no specialized HATS runtime server. All of the necessary runtime information is deployed into an Enterprise Archive (EAR) file and runs in WebSphere Application Server. This IBM Redbooks publication helps you to tailor and configure the new features that are included with HATS V5. Examples and usage scenarios demonstrate how to implement many of the new features and functions, along with those that were present in previous releases of HATS.